DNA barcoding indicates the range extension in an endemic frog Nyctibatrachus jog, from the Western Ghats, India. Issue 9 (2nd September 2021) - Hebbar, Priti; Anand, Anisha; K.V, Gururaja
Abstract: The frogs of genus Nyctibatrachus from the Western Ghats are endemic, with some taxa showing a narrow distribution range. Nyctibatrachus jog was known only from the type locality, Jog falls from Sharavathi river basin suggesting a restricted distribution. In this study, using DNA barcoding, we studied the distribution patterns of N. jog by sampling multiple river basins. 16S rRNA and Cytochrome b genes were used to distinguish N. jog from its congeners as well as to infer intra-species relationships. The results from the 16S rRNA gene showed 99% similarity of the collected individuals with the type specimen from Jog Falls confirming the identity of N. jog . The results indicate that N. jog has wide distribution extending its range in multiple river basins in the Western Ghats, India. This study also provides the Area of Occurrence and Extent of Occurrence of N. jog which could help in developing strategies for its conservation.